Empowering women through digital literacy and education in Cisauk, Tangerang Regency - Vivi Indra Amelia Nasution; Hilma Erfiani Baroroh; Jayanti Armida Sari; Isnaeni Yuliani; Yusrafiddin Yusrafiddin; Muhtarom Muhtarom; Hidayah Hidayah; Arona Fadila (Universitas Muhammadiyah Malang, 2025)
The fast growth of digital technology in today's world makes digital literacy and education more important than ever. Many women in the Cisauk Subdistrict, near BSD City in Tangerang, still lack access to digital knowledge. It becomes difficult for them to support their families and participate in public services, education, and healthcare. To address this issue, the lecturer at Universitas Terbuka initiated a community service program to enhance digital skills among women. The program focused on the integrated health post (Posyandu) cadres, Family Welfare Empowerment Team (TP PKK) members, and homemakers. They took part in discussions, hands-on sessions, and mentoring. The learning was based on four main ideas. These are digital skills, safety, ethics, and culture. The training showed them how to use mobile apps for health, education, finance, and other services. After the program, the women showed familiarity and confidence in using digital tools. They learned how to protect their data, spot false information, and make safe choices when using the internet. Many also began sharing what they learned with their families and neighbours. This program suggests that targeted and locally adapted training initiatives can effectively bridge the digital divide among underserved populations. By equipping women with the skills to navigate digital environments, the program not only enhanced individual agency but also strengthened community-level resilience and participation. The success of this initiative underscores the importance of collaboration with local organizations and the necessity for ongoing support to achieve a lasting impact. Future programs should scale this model to other underserved areas and continue building digital competencies that promote inclusive digital transformation.